The first year of life: home or nursery? (Journal of Parents and Teachers, 2026)
This article reports on a study examining the situation in various countries regarding the care required by babies in their early years, and particularly in the first few months. It therefore addresses the issue of employment arrangements for women following childbirth, which influences the decision to care for the child at home or in a nursery. Finally, it proposes a programme for parents run by the University of Missouri, which consists of activities to be carried out during meetings held throughout the baby’s first year of life, as well as lessons, resources and other materials.
Keywords: the first year of life; motherhood and work; caring for children at home; nursery; the Missouri programme